2012
DOI: 10.1159/000335123
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Blood Vessels: Symptoms, Etiology and Biomechanical Mechanisms

Abstract: Tortuous arteries and veins are commonly observed in humans and animals. While mild tortuosity is asymptomatic, severe tortuosity can lead to ischemic attack in distal organs. Clinical observations have linked tortuous arteries and veins with aging, atherosclerosis, hypertension, genetic defects and diabetes mellitus. However, the mechanisms of their formation and development are poorly understood. This review summarizes the current clinical and biomechanical studies on the initiation, development and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
361
4
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(388 citation statements)
references
References 285 publications
11
361
4
12
Order By: Relevance
“…Hormonal changes, such as elevated estrogen levels, which occur during pregnancy, have been reported to play a major role in the development of varicose veins (27). Alterations in hormonal levels inducing hypertrophy and the growth of the SMC layer in varicose veins have been suggested in different studies (28)(29)(30)(31). However, augmented estrogen levels have also been reported to reduce SMC migration and proliferation (17,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes, such as elevated estrogen levels, which occur during pregnancy, have been reported to play a major role in the development of varicose veins (27). Alterations in hormonal levels inducing hypertrophy and the growth of the SMC layer in varicose veins have been suggested in different studies (28)(29)(30)(31). However, augmented estrogen levels have also been reported to reduce SMC migration and proliferation (17,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about it, abnormal cerebral vascular tortuosity could be an adaptive response to increased flow burden, which manifests mechanical instability in the arterial walls. 37 In tortuous vessels, flow impinges on the outer wall of bends. To make the turn of a bend, flow along the outer curve has to travel at a higher velocity than flow along the inner curve, and has to accelerate.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology and clinical importance of CT are still unclear. CT is associated with increased acute occlusion of coronary arteries, diabetes, and coronary artery fistula [4,15]. CT hampers ventricular function and has been proposed as an indicator of ventricular dysfunction [16].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [15], found that CT was positively correlated with essential hypertension. Tortuosity of coronary arteries is also a common finding seen with hypertension due to elongation and dilatation of the arteries associated with left ventricular hypertrophy [4,15]. The authors assumed that arteries may become tortuous due to reduced axial strain and hypertensive pressure in an elastic cylindrical arterial model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation